Penerapan Kriptografi Vigenere Cipher Pada Kekuatan Kata Sandi - Maulana, Dimas Krisna; Tanjung, Sunilfa Maharani; Ritonga, Reni Septiani; Ikhwan, Ali (Jurnal Sains dan Teknologi (JSIT), 2023)
One of the methods of securing information systems that is commonly known by many people is passwords. Without realizing it, passwords have an important role in securing information that is confidential. In some applications related to software, such as cellphones, ATM cards, and others. There is also a security system that functions similarly to a password. commonly known as a PIN Code. Although it only consists of numbers, its use is the same as a password, which is to secure information. The stored information is usually digital or database-based. Password security aims to secure a password stored in the database, the password needs to be secured because if the password is known by unauthorized parties or who are not entitled then important and other data will be stolen. The password that is secured is a password that is used daily, be it email passwords, social media, databases, operating systems on the device and others into the database. vigenere cipher algorithm to encode the password in a database. The result of this test is that password security is carried out based on the vigenere cipher method using a visual studio application and utilizing a Database with a MySQL application. The end result used is the result of the security process with the result key having no resemblance to the original record. Formation of keys based on user decisions. It is worth paying attention that the key should not be forgotten.